Antiherbivore defenses alter natural selection on plant reproductive traits. (1st April 2016) - Thompson, Ken A.; Johnson, Marc T.J.
Abstract: While many studies demonstrate that herbivores alter selection on plant reproductive traits, little is known about whether antiherbivore defenses affect selection on these traits. We hypothesized that antiherbivore defenses could alter selection on reproductive traits by altering trait expression through allocation trade‐offs, or by altering interactions with mutualists and/or antagonists. To test our hypothesis, we used white clover, Trifolium repens, which has a Mendelian polymorphism for the production of hydrogen cyanide—a potent antiherbivore defense. We conducted a common garden experiment with 185 clonal families of T. repens that included cyanogenic and acyanogenic genotypes. We quantified resistance to herbivores, and selection on six floral traits and phenology via male and female fitness. Cyanogenesis reduced herbivory but did not alter the expression of reproductive traits through allocation trade‐offs. However, the presence of cyanogenic defenses altered natural selection on petal morphology and the number of flowers within inflorescences via female fitness. Herbivory influenced selection on flowers and phenology via female fitness independently of cyanogenesis. Our results demonstrate that both herbivory and antiherbivore defenses alter natural selection on plant reproductive traits. We discuss the significance of these results for understanding how antiherbivore defenses interact with herbivores and pollinators to shape floral evolution.